THE ROLE OF THE AUDITOR’S EXPERIENCE, KNOWLEDGE, AND PROFESSIONAL QUALIFICATION IN AUDITING FINANCIAL STATEMENTS IN LIGHT OF INFORMATION TECHNOLOGY AND ARTIFICIAL INTELLIGENCE TECHNIQUES (A STUDY OF THE OPINIONS OF A SAMPLE OF AUDITORS IN IRAQ) - Mahdi Abbas Abadi; Muhannad Abbas Ayash; Ahmed Ali Salman (Scholar Express Journals, 2024)
The study aims to demonstrate the role of knowledge, experience, and professional and scientific qualification of the auditor in the use of electronic accounting systems, information technology, and artificial intelligence techniques in the field of accounting and auditing. The study was launched in light of the hypotheses specified for it to demonstrate the impact and role of knowledge, experience, and professional qualification in light of the use of the aforementioned techniques in the field of accounting and auditing. The researcher used the theoretical aspect to explain the theoretical aspects that relate to the concepts of experience and professional qualification of the auditor and artificial intelligence techniques. The researcher also used statistical methods through the prepared questionnaire form to prove the research hypotheses. The research sample included a group of auditing companies, auditing offices, and academic specialists. The study reached a set of results, the most important of which is that the academic and practical qualifications of the auditor lead to increasing the accuracy of the results of the audit process, as well as that knowledge and scientific experience in accounting information technology and artificial intelligence techniques give the auditor sufficient opportunity to use this knowledge in preparing reports that lead to improving the quality of the audit process. The study recommended a set of recommendations, the most important of which was emphasizing the need for the accounting and auditing profession to keep pace with the rapid developments in the accounting information technology environment and artificial intelligence techniques, while emphasizing the need for professional organizations specialized in regulating accounting and auditing, following up on the aforementioned developments, and setting a framework and standards that are compatible with the applications of these technologies.
Keywords: Artificial Intelligence; Experience; Knowledge; Professional Qualification